2015
DOI: 10.1007/s40265-015-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery: A Narrative Review of Pharmacotherapy in Pain Management

Abstract: Laparoscopic surgery is widespread, and an increasing number of surgeries are performed laparoscopically. Early pain after laparoscopy can be similar or even more severe than that after open surgery. Thus, proactive pain management should be provided. Pain after laparoscopic surgery is derived from multiple origins; therefore, a single agent is seldom sufficient. Pain is most effectively controlled by a multimodal, preventive analgesia approach, such as combining opioids with non-opioid analgesics and local an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 232 publications
0
52
0
4
Order By: Relevance
“…In our study, all participants underwent laparoscopic surgery, which has been shown to be safe and feasible for treating gynaecological diseases (Prodromidou et al, ). After gynaecological laparoscopy, the main pain areas include incision pain, surgical area pain in the abdominal cavity and other pain in areas such as the shoulder (Sjövall et al, ). We found that the main pain areas after gynaecological laparoscopy from 4 hr after surgery to POD1 and POD2 were surgical area pain in the abdominal cavity and abdominal incision pain (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, all participants underwent laparoscopic surgery, which has been shown to be safe and feasible for treating gynaecological diseases (Prodromidou et al, ). After gynaecological laparoscopy, the main pain areas include incision pain, surgical area pain in the abdominal cavity and other pain in areas such as the shoulder (Sjövall et al, ). We found that the main pain areas after gynaecological laparoscopy from 4 hr after surgery to POD1 and POD2 were surgical area pain in the abdominal cavity and abdominal incision pain (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…They assessed the pain of 100 laparoscopic cholecystectomy patients during the first postoperative week, and the results indicated abdominal incision pain and surgical area pain in the abdominal cavity were most reported pain areas. Another study reported that the surgical area pain in the abdominal cavity and abdominal incision pain after laparoscopic surgery lasted for 2–6 days (Sjövall et al, ). So it is reasonable that surgical area pain in the abdominal cavity and abdominal incision pain in our study were observed from 4 hr after surgery to POD1 and POD2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being most frequently used orally, in recent years, its intravenous use has increased. Its potency is about 1/75 of fentanyl, and in some studies has shown great potency up to 1/60 [48,49].…”
Section: Oxycodonementioning
confidence: 99%
“…www.anesth-pain-med.org cular, subcutaneous, rectal, and epidural [11][12][13][14][15]. Numerous studies have suggested that IV oxycodone is an effective treatment for acute postoperative pain [16,17].…”
mentioning
confidence: 99%